Pro Excel 2007 VBA - DeMarco, Jim (Apress : Imprint: Apress, 2008)
Pro Excel 2007 VBA is the complete guide to creating Excel VBA applications, including coverage of new features in Excel 2007. Covering object-oriented programming techniques, debugging, and error handling methodologies, this book quickly turns novice into expert as it explores COM and .NET components and the advantages of compiled code. The book also covers XML for Excel web development. This book is unique insomuch that author Jim DeMarco is a true expert in the field of Excel programming, and he conveys the Visual Basic for Applications story in the context of the real world. Not just another dry programming guide, Pro Excel 2007 VBA is a journey from novice to expert where the author is your traveling companion. Bon voyage!